Valoração de tecnologias no cenário de transferência de tecnologia entre universidade e empresa no Brasil: uma metodologia proposta - João Leandro Cássio de Oliveira (2020)
This thesis takes as its object the technology transfer between universities and companies, with a focus on valuing technology. In developing countries, such as Brazil, the public sector has greater investment in R&D if compared to the private sector, as it is evidenced by the high capacity for generating patents by Brazilian public universities. Thus, if on one side there are universities with high potential for technology production, on the other side there are companies that need technologies for innovation and competitiveness. It is in this scenario that the Technological Innovation Centers (NIT in Portuguese) fit in. These entities are responsible for the management of the intellectual property of universities, which determines, among other activities, to strengthen the relationship between university and companies, through technology transfer. An important step in the technology transfer process is the valuation of technology, and these centers are responsible for this valuation. Studies such as FORTEC and FORMICT, however, point out the challenges and difficulties that Brazilian NITs face. In this context, this research arises from the following guiding question: how to value technologies in the scenario of technology transfer based on the reality of the Technological Innovation Centers in Brazil? In order to achieve this, the objective of the study is to propose a methodological tool for valuing technologies that attends the Brazilian technology transfer scenario. In methodological terms, the study used different techniques applied to the objectives of each chapter, such as: Scoring and Classification Methods (RAZGAITIS, 2007), Statistical Methods (correlation, regression and hypothesis testing) and Analytic Hierarchy Process (AHP).After the contributions of each chapter, it was possible to propose a valuation method that was called TVT – Technology Valuation Thermometer. Valuation methods based on approaches such as market and income are widespread and practiced, but such methods invariably apply to technologies with a high degree of development, that is, those technologies that have gone through all stages of development and are ready or almost ready for commercialization. This, however, is not the case that Brazilian NITs face, whose technology transfers are at a medium stage of development. In such a way, TVT has some fundamental assumptions: analytical and evaluative capacity of the technology, traceability, identification of potentialities and uncertainties, identification of the degree of development of the technology. Finally, TVT is not a tool that wants to calculate the exact price of a technology, but a value that will serve as a 12 basis for negotiations between universities and companies. Thus, TVT delivers: the trading value of the technology, the value of the up-front fee and the royalty rate related to the current negotiation.